2010
DOI: 10.1017/s0033822200045677
|View full text |Cite
|
Sign up to set email alerts
|

Paleodiet Reconstruction of Human Remains from the Archaeological Site of Natfieh, Northern Jordan

Abstract: ABSTRACT. This investigation concerns human teeth and bones from the site of Natfieh, north Jordan. Nitrogen and carbon isotope analyses were used to model the paleo-economy by reconstructing Natfieh's paleodiet during a specific time period. 14 C dating of human teeth and bones from the site of Natfieh, north Jordan, demonstrate that they belong to the Early Roman period and match the archaeological date from the tomb and grave goods typology. Stable isotope analyses of these humans have provided new informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Yet they gave information on (1) sampling strategy for further studies (e.g., location and anatomical region), and (2) on possible paleodietary differences between Chalcolithic and Bronze Age individuals (Goude et al in press). In Jordan, Al-Shorman (2004) studied the enamel 613C of several Middle/Late Bronze Age individuals buried in three different tombs, and demonstrated that their diet was mainly based on C3 plants, as mentioned also by King (2001) for later periods in the same area (King 2001in Al Bashaireh et al 2010. Finally, a diachronic study conducted in Egypt on Predynastic and Dynastic individuals (ca.…”
Section: Pre-and Protohistorymentioning
confidence: 93%
See 2 more Smart Citations
“…Yet they gave information on (1) sampling strategy for further studies (e.g., location and anatomical region), and (2) on possible paleodietary differences between Chalcolithic and Bronze Age individuals (Goude et al in press). In Jordan, Al-Shorman (2004) studied the enamel 613C of several Middle/Late Bronze Age individuals buried in three different tombs, and demonstrated that their diet was mainly based on C3 plants, as mentioned also by King (2001) for later periods in the same area (King 2001in Al Bashaireh et al 2010. Finally, a diachronic study conducted in Egypt on Predynastic and Dynastic individuals (ca.…”
Section: Pre-and Protohistorymentioning
confidence: 93%
“…Moreover, the Upper Paleolithic and MesolithicNeolithic transition as well as changing food consumptions of costal populations were, and still are, favored research areas (e.g., Richards et al 2001;Pettitt et al 2003;Garcia Guixe et al 2006;Lai et al 2007;Mannino et al 2008). Antiquity and the Middle Ages have been less studied, but research topics on diet, weaning and mobility have increased over the past few years (e.g., Bourbou and Richards 2007;Al Bashaireh et al 2010). …”
Section: Diet In the Mediterranean Region: Some Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were chemically pretreated and dated at the NSF-Arizona Accelerator Mass Spectrometry (AMS) Laboratory following the standard lab protocols. The sample preparation and measurement details were described in Al-Bashaireh et al (2010, 2011. The samples were sonicated in deionized water to remove surface contaminants.…”
Section: Methodsmentioning
confidence: 99%
“…For decades, the stable isotope analysis of bone collagen has been widely used to reconstruct aspects of archaeological human and animal diets from a range of periods and geographical locations (Vogel and Van der Merwe, 1977;Chisholm et al, 1983;Richards et al, 1998;Al-Bashaireh et al, 2010;Petroutsa and Manolis, 2010). The reconstruction of paleodiets using carbon and nitrogen stable isotopes assumes that the 13 C and d 15 N values of the possible components of the diet are known.…”
Section: Carbon and Nitrogen Isotopes And Dietmentioning
confidence: 99%